Osteobiography of a seventh-century potter at the Oupan kiln, China by osteological and multi-isotope approach - Bing Yi (Nature Portfolio, 2019)
Abstract In recent years, the reconstruction of individual life history by the multi-isotope analysis of different skeletal elements has become an active topic in bioarchaeological field. However, most studies focus on the persons with high social status and none cares for craftsmen with low social status. In this study, we undertook a comprehensive analysis on a human skeleton buried in the Oupan kiln, Anhui, China to recover his osteobiography. The archaeological context and dating result (534–644 cal. AD) indicate that he might be a potter at the kiln during the Sui and early Tang Dynasty, characteristic of low social hierarchy. The osteological investigation suggests that he had abnormal vertebrae related to long-term physical labor. In general, the isotopic data demonstrate that he mainly consumed C3(wheat, beans)/C4(millets)-based terrestrial foods. The isotopic (C, N) profiles of dentin sections and isotopic data (C, O) of bone apatite and teeth enamel indicate that he had experienced dramatic dietary changes and/or several migrations throughout the childhood and adulthood. His turbulent life trajectory was highly relevant to his identity and low social status. Our study provides a pilot insight into the life history of craftsmen who was generally overlooked in archaeological, historic and anthropological research.